Whole Brain Imaging of HIV-Infected Patients: Quantitative Analysis of Magnetization Transfer Ratio Histogram and Fractional Brain Volume - Ge, Yulin; Kolson, Dennis L.; Babb, James S.; Mannon, Lois J.; Grossman, Robert I. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Magnetization transfer ratio (MTR) histogram analysis and volumetric MR imaging are sensitive tools with which to quantify the tissue destructive effects in patients with white matter or neurodegenerative disease. Our purpose was to determine whether whole brain MTR and fractional brain parenchyma volume measurements are altered in HIV-1-infected patients who are neurologically symptomatic and in those who are asymptomatic.METHODS: We performed MR imaging and MTR studies of 15 neurologically symptomatic (seven patients) and asymptomatic (eight patients) HIV-1-seropositive patients and compared their findings with those of 10 seronegative normal control participants. MTR was computed on the basis of whole brain parenchyma segmented by using thin section dual echo MR images.RESULTS: The loss of brain tissue, indicated by fractional brain parenchyma volume, was more pronounced in neurologically symptomatic patients (P = .003) but not in asymptomatic patients (P = .23) when compared with control participants. As for whole brain MTR histogram analysis, both patient groups showed significant decrease in mean (P = .02) and median (P ≤ .009) values, compared with normal control participants. There was a trend toward positive correlation (r ≥ 0.56) between MTR histogram statistics and fractional brain parenchyma volume.CONCLUSION: Our results suggest that MTR histogram analysis is sensitive in detecting early involvement in neurologically asymptomatic patients with HIV and may, therefore, be used as a combined tool with volumetric measurement, which showed significant tissue loss only in symptomatic patients, to assess various stages of brain damage induced by HIV.